Environmental Impact Assessment of Boga Bridge Patukhali - Islam, MH; Faisal, M; Mahmood, KA (Journal of Environmental Science and Natural Resources, 2015)
The economic development and social unity largely depend on the communication facilities. Improvement of national highway network in Bangladesh has been obstructed due to some rivers. Lohalia is one of the largest rivers in Patuakhali district divides Bauphal and Dumki upazila. The major transport barrier between the Bauphal and Patuakhali, Barisal city is Boga Bridge. The proposed 900 meter long Boga Bridge will be constructed under the supervision of World Bank, ADB, local and international experts. This paper shows the environmental impact assessment of Boga Bridge over the Lohalia River. The aim of the study is to identify the major environmental impact, mitigation measures and environmental impact value of the Boga Bridge. The major impacts of the Boga Bridge are loss of livelihood, loss of land, delta formation, loss of trees and rare species, loss of fisheries, navigational restrictions, surface water pollution, air pollution, soil contamination, river bank erosion, change the river flow. The environmental impact value of this project is 3 (negative three). The mitigation measures for the Boga Bridge project are cash compensation, relocation, periodic dredging, plant two for one felled, provide new jobs, revetment, provide safe water, good food and sanitation etc. By the proper implementation of these mitigation measures must help to reduce these impacts. J. Environ. Sci. & Natural Resources, 8(1): 73-77 2015